2017
DOI: 10.1242/bio.023960
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic frequency response patterns in mechano-sensory neurons of the leech

Abstract: Animals employ mechano-sensory systems to detect and explore their environment. Mechano-sensation encompasses stimuli such as constant pressure, surface movement or vibrations at various intensities that need to be segregated in the central nervous system. Besides different receptor structures, sensory filtering via intrinsic response properties could provide a convenient way to solve this problem. In leech, three major mechano-sensory cell types can be distinguished, according to their stimulus sensitivity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…More specifically, a possible explanation to the different sensitivity to US of P and N cells could lie on the recent finding of frequency specificity of the classes of mechanosensory neurons in the leech [33] . In this work the authors find that N cells are effectively low-pass filtering voltage oscillations while P cells act as high pass filters.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, a possible explanation to the different sensitivity to US of P and N cells could lie on the recent finding of frequency specificity of the classes of mechanosensory neurons in the leech [33] . In this work the authors find that N cells are effectively low-pass filtering voltage oscillations while P cells act as high pass filters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that excitotoxicity may be a contributing factor to pancreatic β-cell failure, in both type 1 diabetes and type 2 diabetes 69,70 . Interestingly, we observed an increase in action potential frequency and a decrease in AP firing threshold in Scn9a KO β-cells, indicating that these cells have increased excitability by some definititions 72 . Elevation in the intracellular Ca 2+ concentration has been found in rat islets, exposed to prolonged high glucose 71 , and mice with dysfunctional K ATP channels exhibiting chronic, continuous action potential firing 5 .…”
Section: Discussionmentioning
confidence: 72%
“…При сильном болевом воздействии на стенку тела животного N-механочувствительные нейроны генерируют низкочастотные спайки от 0,5 до 2 Гц. Слабое давление или поглаживание вызывает активацию механосенсорных клеток T-типа, генерирующих высокочастотные разряды от 5 до 12 Гц, механосенсорные нейроны P-типа генерируют разряды средней частоты (Fischer et al 2017). Поскольку НР имеет синаптическую связь с механосенсорными нейронами (De-Miguel, Nicholls 2015;Fischer et al 2017;De-Miguel, Trueta 2005), то, следовательно, и in vivo он может получать раздражающее воздействие самой различной частоты, тесно связанной с жизнедеятельностью животного.…”
Section: взаимодействие между нервной и секреторной функциями при синunclassified